2014
DOI: 10.1007/s11802-015-2348-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of wet waste from shrimp (Litopenaeus vannamei) with or without sea mud to feeding sea cucumber (Stichopus monotuberculatus)

Abstract: In the present study, the applicability of the wet waste collected from shrimp (Litopenaeus vannamei) to the culture of sea cucumber (Stichopus monotuberculatus) was determined. The effects of dietary wet shrimp waste on the survival, specific growth rate (SGR), fecal production rate (FPR), ammonia-and nitrite-nitrogen productions of sea cucumber were studied. The total organic matter (TOM) level in the feces of sea cucumber was compared with that in corresponding feeds. Diet C (50% wet shrimp waste and 50% se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…71,72 Nevertheless, in a feeding trial, lowest growth was reported when Stichopus monotuberculatus was fed only waste from a shrimp farm, compared with a commercial sea cucumber diet or a mixed diet of 50% waste from the shrimp farm and 50% sea mud. 73 Only a limited number of studies used the balance method to determine waste extraction efficiencies, and they do show that sea cucumbers reduce aquaculture waste. Sea cucumbers can extract 0.1%-20% OM, 3%-10% organic C, 7%-16% organic N and 21%-25% 2).…”
Section: Sea Cucumbers or Polychaetesmentioning
confidence: 99%
See 2 more Smart Citations
“…71,72 Nevertheless, in a feeding trial, lowest growth was reported when Stichopus monotuberculatus was fed only waste from a shrimp farm, compared with a commercial sea cucumber diet or a mixed diet of 50% waste from the shrimp farm and 50% sea mud. 73 Only a limited number of studies used the balance method to determine waste extraction efficiencies, and they do show that sea cucumbers reduce aquaculture waste. Sea cucumbers can extract 0.1%-20% OM, 3%-10% organic C, 7%-16% organic N and 21%-25% 2).…”
Section: Sea Cucumbers or Polychaetesmentioning
confidence: 99%
“…For both sea cucumbers and polychaetes, lower growth has been reported when feeding fish faeces, as compared with commercial diets, 73,78,99 suggesting that waste quality is not sufficient to sustain optimal growth. For mussels, it has also been suggested that fish faeces alone is insufficient; integration of M. edulis with Atlantic cod in a closed system resulted in nutritionally stressed mussels.…”
Section: Waste Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another species, Stichopus monotuberculatus , has shown promise for the utilization of shrimp farming waste as part of the sea cucumber diet in southern China (Chen et al . ,b). It has also been shown that sea cucumbers ( P. californicus , H. forskali, H. leucospilota and A. japonicus ) can reduce the impact of fish farm activities, by reducing the organic carbon and nitrogen content of the high organic content faeces of the fish by up to 60%, reducing waste biodeposition (Ahlgren ; Yu et al .…”
Section: Commercial and Experimental Integration Of Sea Cucumbers Intmentioning
confidence: 99%
“…The co-culture of shrimps and sea-cucumbers (Purcell et al, 2006;Xu and Zhu, 2002), or their polyculture with jellyfish (Li et al, 2014b(Li et al, , 2014a has therefore been considered as an alternative to limited the organic matter excess from shrimp monocultures. Moreover, studies revealed that shrimp wastes could be used to feed sea cucumbers (Chen et al, 2015a(Chen et al, , 2015b. These co-culture systems could (1) limit sediment organic enrichment (Slater and Carton, 2007) and (2) develop a new high value exportation pathway.…”
Section: Introductionmentioning
confidence: 99%